2017
DOI: 10.1002/ejoc.201601653
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Functionalization of Heteroarenes by Use of Photoredox Catalysis

Abstract: Abstract:The functionalization and the construction of heteroarenes with the aid of visible-light photoredox catalysis have been investigated by a number of research groups. In this review, two different approaches are reported. In the first part, substitution of different heteroaryl derivatives is presented according to four classes of reactions: alkylation, perfluoroalkyl-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 169 publications
0
18
0
Order By: Relevance
“…Transition-metal photocatalysts and organic dyes have granted chemists access to ever increasing alternatives to classical radical chemistry transformations as well as unconventional reactivity in the discovery of new organic transformations. 1 Implementation of photochemical processes is preferential to the classical, thermal methods of radical generation, as they often eliminate the need for radical initiators, stoichiometric additives and harsh reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Transition-metal photocatalysts and organic dyes have granted chemists access to ever increasing alternatives to classical radical chemistry transformations as well as unconventional reactivity in the discovery of new organic transformations. 1 Implementation of photochemical processes is preferential to the classical, thermal methods of radical generation, as they often eliminate the need for radical initiators, stoichiometric additives and harsh reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Since the pioneer works by Gafney and Adamson, who showed that singleelectron-transfer (SET) event can be initiated by the triplet charge-transfer excited state of [Ru(bpy) 3 ] 2+ , [16] the application of polypyridine-metal complexes with metal-ligand charge transfer (MLCT) properties in catalysis has become a useful alternative approach to create new C-C bonds, [17][18][19][20][21][22][23][24][25][26] and more recently to functionalize C-H bonds. [27][28][29][30] The first photoredox functionalization of C(sp 2 )-H bond was reported in 1984 by Deronzier with the [Ru(bpy) 3 ] 2+ -assisted the cyclization of stilbenediazonium salts. [31] Photoredox catalysts (PC n ), such as tris (2,2′-bipyridine) ruthenium (II) [Ru(bpy) 3…”
Section: Introductionmentioning
confidence: 99%
“…To date, many groups, especially MacMillan and Molander, have made a number of elegant contributions, and thus this method has become a powerful tool in the synthesis of azaarene derivatives. [14] In view of distinct characteristics of these strategies and the corresponding published reviews, [10,12,14,15] to elucidate strategies for exploiting the electron-withdrawing abilities of azaarenes stemming from the structurally embedded C=N bonds in photoredox catalysis, in this review, we will discuss the advances in the synthesis of azaarene derivatives via Strategy B and Strategy D from their respective first examples to April 2020.…”
Section: Introductionmentioning
confidence: 99%
“…In view of distinct characteristics of these strategies and the corresponding published reviews, to elucidate strategies for exploiting the electron‐withdrawing abilities of azaarenes stemming from the structurally embedded C=N bonds in photoredox catalysis, in this review, we will discuss the advances in the synthesis of azaarene derivatives via Strategy B and Strategy D from their respective first examples to April 2020.…”
Section: Introductionmentioning
confidence: 99%